2018
DOI: 10.1080/03639045.2018.1442844
|View full text |Cite
|
Sign up to set email alerts
|

In vitroandin vivoevaluation of cyclodextrin-based nanosponges for enhancing oral bioavailability of atorvastatin calcium

Abstract: The aim of this study was to explore the feasibility of complexing the poorly water-soluble drug atorvastatin calcium (AC) with β-cyclodextrin (β-CD) based nanosponges (NS), which offer advantages of improving dissolution rate and eventually oral bioavailability. Blank NS were fabricated at first by reacting β-CD with the cross-linker carbonyldiimidazole at different molar ratios (1:2, 1:4, and 1:8), then NS of highest solubilization extent for AC were complexed with AC. AC loaded NS (AC-NS) were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…A significant difference in drug loading was observed in between 1:3 w/w and 1:4 w/w. However, no further change in drug loading was seen in between 1:4 w/w and 1:5 w/w might be due to saturation solubility of KYNA (Zidan et al, 2018).…”
Section: Physicochemical Characterization Of Ns and Kyna Loaded Nsmentioning
confidence: 91%
See 1 more Smart Citation
“…A significant difference in drug loading was observed in between 1:3 w/w and 1:4 w/w. However, no further change in drug loading was seen in between 1:4 w/w and 1:5 w/w might be due to saturation solubility of KYNA (Zidan et al, 2018).…”
Section: Physicochemical Characterization Of Ns and Kyna Loaded Nsmentioning
confidence: 91%
“…KYNA loaded nanosponge was prepared by the freeze-drying method as established earlier (Zidan, Ibrahim, Afouna, & Ibrahim, 2018). An aqueous suspension of individual nanosponges (β-CDNS1 to β-CDNS3) was prepared (10 mg/ml) and the required quantity of KYNA was added into it at different weight ratio of 1:3, 1:4 and 1:5 (w/w), respectively.…”
Section: Preparation Of Kyna Loaded Nanospongementioning
confidence: 99%
“…Nanosponge has a unique property of forming nanosuspension, when vapor is dispersed. 10 Paracetamol is world's most widely over-the-counter prescribed analgesic. It is the rst step of medication in the WHO pain scale, and is widely prescribed through many international recommendations as rst-line pharmacological treatment for acute and chronic painful conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The prepared nanosponges were found to increase bioavailability of drug up to 2.13-folds in comparison to its suspension. In addition, pharmacokinetic studies revealed remarkable decrease in total cholesterol, LDL-C (Low Density Lipoprotein Cholesterol) and triglyceride and improved level of HDL-C (High Density Lipoprotein Cholesterol) leading to improvement of liver steatosis [117].…”
Section: Oral Drug Deliverymentioning
confidence: 99%